Game-Based Kitabah Learning Innovation Using Smart Apps Creator at Pondok Pesantren Raudhatus Sakinah - Jannah, Kholifah Roudhatul; Sari, Putri Dian; Imron, Kristina; Qaaf, Muhammad Alfath (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This study aims to develop a writing (kitabah) learning media based on a game using Smart Apps Creator (SAC) to enhance Arabic writing skills at Pondok Pesantren Raudhatus Sakinah, Ogan Komering Ilir Regency, South Sumatra. The type of research used is Research and Development (R&D) with the Borg and Gall model approach. The research subjects include 14 eighth-grade students and the Arabic language teacher at the pesantren. Data collection techniques involved questionnaires, tests, as well as interviews and observations. Quantitative data was gathered through pre-tests and post-tests to measure students' writing improvements after using the learning media, while qualitative data was obtained from interviews with teachers and observations during the media usage. Data analysis techniques included quantitative analysis using the Wilcoxon test to examine significant differences between pre-test and post-test scores, and qualitative analysis using the Miles and Huberman model to reduce, display, and draw conclusions from the collected data. The results show that the SAC-based learning media is valid according to assessments from content and media experts, and there is a significant improvement in students' writing skills after using the media, with the Wilcoxon test showing a significance value of less than 0.05. The implications of this research indicate that SAC-based game media can serve as an effective alternative to improve Arabic writing skills in pesantren, as well as provide prospects for further development of interactive learning media in other educational institutions.